2016
DOI: 10.1002/jez.2037
|View full text |Cite
|
Sign up to set email alerts
|

A Threshold Dosage of Testosterone for Female‐to‐Male Sex Reversal in Rana rugosa Frogs

Abstract: Androgens play a critical role in testicular differentiation in many species of vertebrates. While female-to-male sex reversal can be induced by testosterone (T) in some species of amphibians, the mechanism still remains largely unknown even at the histological level. In this study, we determined a threshold dosage of T to induce female-to-male sex reversal in the Japanese frog Rana (R.) rugosa. Tadpoles were allowed to metamorphose into frogs with T present in the rearing water. At 0.2 ng/mL T, female frogs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Previously it has been shown that female-to-male sex-reversal is not induced when an ovary is treated with T at 0.02 ng/ml in rearing water of R . rugosa tadpoles [16]. However, in the present study, the average sizes of the Tg ZW gonads at 0.02 ng/ml of T became significantly smaller than those of the pTg ZW gonads (Fig 1, 1.6±0.9 vs 4.3±0.5 mm, P<0.01).…”
Section: Resultscontrasting
confidence: 56%
“…Previously it has been shown that female-to-male sex-reversal is not induced when an ovary is treated with T at 0.02 ng/ml in rearing water of R . rugosa tadpoles [16]. However, in the present study, the average sizes of the Tg ZW gonads at 0.02 ng/ml of T became significantly smaller than those of the pTg ZW gonads (Fig 1, 1.6±0.9 vs 4.3±0.5 mm, P<0.01).…”
Section: Resultscontrasting
confidence: 56%
“…All the animal experiments in this study were performed with respect to Fundamental Guidelines for Proper Conduct of Animal Experiments and Related Activities in Academic Research Institutions and the Prevention of Cruelty to Animal Act, and with official approval from the Committee of Animal Experimentation of Waseda University, as described previously (Oike, Kodama, Nakamura, & Nakamura, ).…”
Section: Methodsmentioning
confidence: 99%
“…The expression level of dmrt1 is high in mature testis of black porgy Acanthopagrus schlegeli during sex-reverse process (48). Besides fish species, T-treated ovaries induce upregulated expression of dmrt1 in the ovotestis of Rana rugosa Frogs (49). Aoyama et al (50) revealed that dmrt1 was not transcribed at any time during ovarian development but was expressed in the female-to-male sex reversed gonad of amphibians.…”
Section: Discussionmentioning
confidence: 99%